Epidemiology of birth defects based on surveillance data from 2011-2015 in Guangxi, China: comparison across five major ethnic groups - Jichang Chen; Xuemei Huang; Bo Wang; Yu Zhang; Chokechai Rongkavilit; Dingyuan Zeng; Yongjiang Jiang; Ba Wei; Chawla Sanjay; Eric McGrath (BMC, 2018)
Abstract Background The causes of birth defects (BDs) are complex and include genetic and environmental factors and/or their interactions. More research is needed to describe the epidemiology of BDs within specific regions of China. This study focused on differences in the prevalence of BDs based on ethnicity in a large city in Guangxi Province, China. Methods Surveillance data of infants born in 114 registered hospitals in Liuzhou between 2011 and 2015 were analyzed to determine the epidemiology of BDs across five major ethnic groups. We calculated the prevalence of BDs and relative risk of BDs by ethnicity. Results There were 260,722 perinatal infants of which 6581 had BDs, with the average prevalence of 25.24 per 1000 perinatal infants (PIs). Prevalence data showed an obvious uptrend over the past 5 years. Han had the highest prevalence of total BDs (28.98‰), followed by Zhuang (25.19‰), Yao (18.50‰), Miao (15.78‰) and Dong (14.24‰). Relative to the Han; Zhuang, Miao, Yao, and Dong had a lower risk of musculoskeletal and urogenital malformations; Miao and Yao had a lower risk of cardiovascular malformation; and Dong had a lower risk of cardiovascular and craniofacial malformation. Several maternal risk factors were found to be associated with BDs (e.g., maternal and gestational age, number of antenatal care visits). Conclusion This study provided a comprehensive description of ethnic differences in the risk of BDs in Liuzhou City, China. Observed ethnic differences in the risk of BDs may be related to genetic susceptibilities, environment, cultural customs, or to potential combinations of these factors.